Nonlinear relation between pulse pressure and coronary heart disease in patients with type 2 diabetes or hypertension. Issue 5 (May 2016) - Nargesi, Arash A.; Esteghamati, Sadaf; Heidari, Behnam; Hafezi-Nejad, Nima; Sheikhbahaei, Sara; Pajouhi, Atieh; Nakhjavani, Manouchehr; Esteghamati, Alireza
Abstract : Objectives: Wide pulse pressure (PP) is an independent predictor of coronary heart disease (CHD). However, the linearity of the relation between PP and CHD was not examined before. We aimed to examine this relation in patients with type 2 diabetes and/or hypertension. Methods: A total of 3120 patients (including 2607 with diabetes and 1586 with hypertension) were followed for 7.8 years. Physician-adjudicated first hard CHD event was the primary outcome. Cox regression analysis was used to investigate the association between PP and incident CHD. Restricted cubic splines were used to investigate nonlinear relations. Results: Four spline covariates were defined between 30, 40, 50, 60, and 70 mmHg. The null-hypothesis of the linearity of the relation between PP and CHD was rejected ( P value = 0.004). The second, third, and fourth spline covariates were significant ( P value = 0.02, P value = 0.02 and P value = 0.01, respectively), supporting a nonlinear relation in corresponding PP intervals. Patients with PP less than 45 mmHg and PP more than 55 mmHg had increased risk of future CHD event, compared with those with PP between 45 and 55 mmHg [hazard ratio (HR) = 1.33 (1.00–1.77) and HR = 1.67 (1.23–2.27), respectively]. This remained significant after controlling for systolic, diastolic, or mean arterial pressures in wide PP group. However, adjustment for traditional cardiovascular risk factors (especially age) attenuated the relation in those with wide PP. Conclusion: The relation between PP and CHD is nonlinear in patients with type 2 diabetes and hypertension. Both narrow and wide PPs increase risk of future hard CHD events. The association between wide PP and CHD is independent from SBP, DBP, or mean arterial pressure. Abstract : Supplemental Digital Content is available in the text